Problematika Pembentukan Komponen Cadangan: Dilema Partisipasi Bela Negara di Tengah Ancaman Pemutusan Hubungan Kerja - Aditama Candra Kusuma; Aji Lukman Ibrahim (JURNAL SOSIAL HUMANIORA (JSH), 2022)
The issue that arises during the formation of the Reserve Component is the employer's termination of workers who follow the Reserve Component. This study aims to determine the sanctions for employers who terminate the employment of workers who participate in the selection of Reserve Components, as well as the ideal future arrangement for employers who terminate the employment of workers who participate in future selections. In this study, qualitative descriptive and data analysis techniques are presented in accordance with normative legal research methods. So that the results obtained are that the appropriate sanctions for employers who terminate employment, namely criminal sanctions, refer to the criminal provisions in Law No. 23 of 2019 on the Management of National Resources for National Defense, as well as ideal future arrangements for employers who terminate employment relationships, namely by imposing criminal provisions which must first be reformulated in Article 78 paragraph (1) of Law No. 23 of 209 on the Management of National Resources for National Defense.